2019
DOI: 10.1038/s41598-019-44954-1
|View full text |Cite
|
Sign up to set email alerts
|

The zinc transporter Zip14 (SLC39a14) affects Beta-cell Function: Proteomics, Gene expression, and Insulin secretion studies in INS-1E cells

Abstract: Insulin secretion from pancreatic beta-cells is dependent on zinc ions as essential components of insulin crystals, zinc transporters are thus involved in the insulin secretory process. Zip14 (SLC39a14) is a zinc importing protein that has an important role in glucose homeostasis. Zip14 knockout mice display hyperinsulinemia and impaired insulin secretion in high glucose conditions. Endocrine roles for Zip14 have been established in adipocytes and hepatocytes, but not yet confirmed in beta-cells. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In primary human islets, NTBI uptake is mediated by the zinc transporter ZIP14 (SLC39A14), which localises to the plasma membrane of beta-cells, where iron loading is restricted. Chronic (24 h) high glucose levels upregulate the transporter expression, thus confirming the functional relevance of ZIP14 and suggesting possible consequences in iron homeostasis [ 34 ]. However, siRNA-mediated ZIP14 knockdown determined only a 50% reduction of NTBI uptake, suggesting that other transport systems may be involved as well.…”
Section: Iron-homeostasis In Beta-cellsmentioning
confidence: 84%
See 1 more Smart Citation
“…In primary human islets, NTBI uptake is mediated by the zinc transporter ZIP14 (SLC39A14), which localises to the plasma membrane of beta-cells, where iron loading is restricted. Chronic (24 h) high glucose levels upregulate the transporter expression, thus confirming the functional relevance of ZIP14 and suggesting possible consequences in iron homeostasis [ 34 ]. However, siRNA-mediated ZIP14 knockdown determined only a 50% reduction of NTBI uptake, suggesting that other transport systems may be involved as well.…”
Section: Iron-homeostasis In Beta-cellsmentioning
confidence: 84%
“…Iron also directly controls ATP synthesis because, as an Fe-S cluster protein, it is part of the complexes I, II, III and IV of the mitochondrial respiratory chain. In line with this possibility, in the Ins-1E-β-cell line, ZIP14 silencing decreases iron transport into the cells and downregulates the expression of many metal-binding proteins, such as the cytoplasmic iron-sensing protein aconitase 1 (ACO1) and ribosomal mitochondrial proteins, thus affecting oxidative phosphorylation and insulin release [ 34 ].…”
Section: Iron Is Required For the Normal Beta-cell Functionmentioning
confidence: 99%
“…Consistent with this, knockdown of ZIP13 reduced osteogenic gene MSX2 and ALPL mRNA expression in hVICs. ZIP14 is responsible for zinc uptake by cells 35 , and has been reported to be a critical regulator of glucose homeostasis and beta-cell function 35,36 . We found that knockdown of ZIP14 in hVICs attenuated calcium deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the two zinc importers that showed changed expression in ZnT8 haploinsufficient cells were ZIP8 and ZIP14, which both have functions in the immune response [58,59]. ZIP14 expression has also been linked to insulin content, processing, and secretion in INS-1E β-cells [60]. Further, since ZnT8 expression is not restricted to β-cells [61,62], polymorphisms may induce effects systemically.…”
Section: Discussionmentioning
confidence: 99%